The Effectiveness of Al2SO4, CaO and Crude Tannin Extract Originated From Averrhoa bilimbi Leaf to Improve the Quality of Peat Water - Fahrurozi, Muhammad Arif; Harahap, Sampe; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Peat wateris classified as low quality water because it has dark color, high organic matter content, high TDS, high turbidity and low pH. The crude tannins extract have been used for improving river water, but there is no information on the use of crude extrac ttannins from Averrhoa bilimbi leaf in improving the quality of peat water. To understand the effectiveness of crude tannin extracted from Averrhoa bilimbi leaf in improving the peat water quality, a study has been conducted from May to October 2015. There was CRD method applied, with 4 treatments, namely P0 (control, withhout tannin extract), P1(10 mlL-1), P2(20 mlL-1) and P3(30 mlL-1). In each treatment unit, 8 liters peat water was added with Alum (Al2SO4) (0.25grL-1) and lime (CaO) (0.3grL-1) and then was added with various dosages of tannin extract. The treated water was kept for 3 hours and the water quality parameters were measured. The treated water was then used to rear Cyprinus carpio.Results shown that the treated water quality was improved, there was degradation in organic matter content, turbidity and colour, while pH, DO and TDS was increase. The best treatment was obtained in P2, as the organic matter decrease, from 1,211.33 to 21,480 mg/L, the turbidity decrease, from 951.33 to 30.73 NTU and the color also decrease, from 29,000.33 to 693 PtCo. The highest survival rate of C. carpio after being reared for 4 days was also found in the P1 treated water, that was 96.66%. Based on data obtained, it can be concluded that the crude tannins extracts from A. Bilimbi leaf is effective to improve the quality of peat water.Keywords : Peat Water, tannins, Cyprinus carpio, Averrhoa bilimbi leaf